Incidence and risk factors of acute renal injury after Stanford type A aortic dissections - XU Xiao; LI Xiaodong; WEN Jing (陆军军医大学学报, 2025)
Objective‍　‍To explore the occurrence of acute kidney injury (AKI) in patients with Stanford type A aortic dissection (TAAD) after surgical treatment, analyze the risk factors, and construct a prediction model. Methods‍　‍A retrospective case-control study was conducted on 138 TAAD patients undergoing surgical treatment in our hospital from January 2016 to June 2024. After Kidney Disease Improving Global Outcomes (KDIGO) criteria was performed within 1 week after surgery, they were divided into AKI (n=95) and non-AKI (n=43) groups. Univariate and multivariate logistic regression analyses were performed to identify the perioperative risk factors. Then a nomogram model were constructed, and receiver operating characteristic (ROC) curve was plotted to analyze its predictive efficacy. Results‍　‍The incidence of postoperative AKI was 68.84% (95 cases) in the TAAD patients, including 51.58% (49 cases) of stage 3 AKI and 38.95% (37 cases) requiring continuous renal replacement therapy. The length of ICU stay, time to extubation, and abandonment of treatment were significantly higher in the AKI group than the non-AKI group (P<0.001). Multifactorial analysis showed that the monocyte count on postoperative day 1 (OR=3.521) and preoperative creatinine level (OR=1.019) were independent risk factors for AKI, postoperative uric acid level (OR=1.005) was correlated with AKI, and intraoperative urine volume (OR=0.739) and globulin level at 1 d postoperatively (OR=0.781) were protective factors. The area under the ROC curve of the constructed model was 0.866, with a sensitivity of 0.811 and a specificity of 0.791. Conclusion‍　‍Postoperative AKI occurrence can be reduced in TAAD patients by optimizing the intraoperative urine output, modulating the postoperative inflammatory response, and strengthening nutritional support. Our prediction model for AKI risk is of significance for early clinical identification of high-risk patients in TAAD patients after surgical treatment.